Comparative results of radius distal AO type C1 fractures of elderly women by two different techniques - Yigit, Şeyhmus (Acta Biomedica Atenei Parmensis, 2020)
ackgrounds: We evaluated clinical and radiographic outcomes of volar locking plates and close reduction with percutaneous pinning treatment approaches for elderly female patients with AO type C1 simple intra-articular distal radius fractures. Patients and Methods: We conducted retrospective studies of 72 elderly female patients with AO type C1 simple intra-articular DRFs treated with VLPs or CRPP, from 2012 to 2018. The patients were divided into two groups: There were 38 patients in VLP group and 34 patients in CRPP group. Periodic clinical and radiological evaluation was performed at 2nd, 4th, 6th, 8th weeks and in 6 and 12 months intervals for all patients. We recorded the patient-rated wrist evaluation scores, flexion, extension, supination and pronation degrees and radiographic outcome scores at the end of 6th and 12 months after surgery. Results: A total number of 72 patients were studied. 38 patients were treated with VLP and 34 patients were treated with CRPP .The mean age of the patients was 70,5 years. Comparing the PRWE scores, the VAS scores and the ROM degrees between the 2 groups yielded no significant difference at any time point between 6 months and 1 year. There were no differences in radiographic outcomes at the latest reported follow up between the two interventions and there was no significant difference in the complication between the 2 groups (VLP 6 and CRPP 6) complications. Conclusions: Complicated surgeries should be avoided because of specific problems in women aged 60 years or older. Our study show that VLP and CRPP techniques had little differences and similar clinical and radiographic results.